Numerical study of water control with downhole oil-water separation technology - Yin, K.Y. (EDP Sciences, 2014)
The maturing oil fields with increasing water production can pose a challenging produced water handling and disposal issues. This paper presents a numerical study of a motorless hydrocyclone to enhance understanding of the downhole oil-water separation. The turbulence of fluid flow is obtained using K-Îµ Realizable Turbulence model for complex swirl dominated flow, while the interface between hydrocarbon and water is described using the Discrete Phase model. In this approach, factors which contribute to the hydrocyclone separation instability were discussed. Discussion is then extended to the relationship of residence time with pressure difference between overflow and underflow. These pressure differences are able to relate to pressure condition for high water cut well which require downhole separation. Â© 2014 Owned by the authors, published by EDP Sciences.